1999
DOI: 10.1002/(sici)1097-0142(19990401)85:7<1439::aid-cncr3>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Staining of interleukin‐10 predicts clinical outcome in patients with nasopharyngeal carcinoma

Abstract: The results imply that expression of IL-10 is a prognostic factor in patients with NPC and may prove valuable in selecting patients with NPC who are candidates for aggressive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
(23 reference statements)
1
13
1
Order By: Relevance
“…In NPC, some studies found an increased production of IL‐10 suggesting a possible involvement in the tumour growth; however, opposite findings have also been reported. Previous studies have showed increased IL‐10 expression in epithelial NPC cells and IL‐10 serum level associations with undifferentiated NPC and clinical late stage (Yao et al ., 1997; Fujieda et al ., 1999; Budiani et al ., 2002), while others reported no detectable NPC cell expression of IL‐10 and no association with serum levels (Beck et al ., 2001; Tan et al ., 2006). Data on Tunisian patients indicate that tumour‐infiltrating lymphocytes of undifferentiated NPC produced more IL‐10 than their own peripheral blood lymphocytes, suggesting the possibility of an imbalance in immunoregulatory cytokines production in NPC (Fliss‐Jaber et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In NPC, some studies found an increased production of IL‐10 suggesting a possible involvement in the tumour growth; however, opposite findings have also been reported. Previous studies have showed increased IL‐10 expression in epithelial NPC cells and IL‐10 serum level associations with undifferentiated NPC and clinical late stage (Yao et al ., 1997; Fujieda et al ., 1999; Budiani et al ., 2002), while others reported no detectable NPC cell expression of IL‐10 and no association with serum levels (Beck et al ., 2001; Tan et al ., 2006). Data on Tunisian patients indicate that tumour‐infiltrating lymphocytes of undifferentiated NPC produced more IL‐10 than their own peripheral blood lymphocytes, suggesting the possibility of an imbalance in immunoregulatory cytokines production in NPC (Fliss‐Jaber et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…SCCHN cells also produce significant IL-10 (13), and IL-10 in SCCHN has been intensively studied. Several groups have reported that IL-10 immunohistochemical staining correlated with clinical outcome in patients with nasopharyngeal carcinoma (102,103), and that IL-10 expression is also associated with FasL (104). In laryngeal SCC, serum IL-10 level was significantly correlated with disease activity and TNM classification (105).…”
Section: Tumor Sidementioning
confidence: 98%
“…ESPITE RECENT DEVELOPments in the understanding of cancer at the level of regulatory protein expression, the direct clinical relevance of squamous cell carcinomas of the head and neck (HNSCCs) still remains unclear. To find an independent prognostic factor for patients with HNSCCs, we investigated the expression of tumorassociated factors from all angles, including cytokines and cytokine receptors (granulocyte colony-stimulating factor [G-CSF], interleukin 10 [IL-10], G-CSF receptor [G-CSFR], and IL-12 receptor [IL-12R]) [1][2][3] ; angiogenic factors (plateletderived endothelial cell growth factor [PD-ECGF] and endothelial cell marker for a blood microvessel [CD34]) 4 ; cell cycle-related proteins (p27, cyclin D1, and cyclin E) [5][6][7] ; apoptosis-related factors (wildtype p53 [wt-p53], Bax, Bcl-2, apoptotic index, Fas, and Fas ligand [FasL]) 8,9 ; oncogene proteins (c-fos and c-Myc); cell surface proteins (P-glycoprotein [P-gp], multidrug resistance-associated protein [MRP], nm23, and CD40) [10][11][12] ; intracellular proteins (aryl hydrocarbon receptor nuclear translocator [Arnt], aryl hydrocarbon receptor, and heat shock protein 27); and DNA mismatch-repair protein (protein encoded by human mutL homologue 1 [hMLH1] and the human mutS homologue of the chromosome 2p gene [hMSH2]). 13 Granulocyte colony-stimulating factor regulates the proliferation and differentiation of granulocytic progenitor cells and ac-tivated mature neutrophils through G-CSFR.…”
mentioning
confidence: 99%
“…18 In the case of nasopharyngeal carcinoma, there was a significant difference in overall survival rates between the negative and positive expressions of IL-10. 2 Interleukin 12 plays an important role in host defense against several tumors by an increased ability to induce apoptosis in cancer cells through IL-12R. 19 Platelet-derived endothelial cell growth factor is a potent factor in the stimulation of endothelial cell migration and proliferation.…”
mentioning
confidence: 99%